2018
DOI: 10.3762/bjoc.14.238
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of functionalised β-keto amides by aminoacylation/domino fragmentation of β-enamino amides

Abstract: Ethylenediamine-derived β-enamino amides are used as equivalents of amide enolate synthons in C-acylation reactions with N-protected amino acids. Domino fragmentation of the obtained intermediates leads to functionalised β-keto amides, bearing a protected amino group in their side chain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…N-protected γ-amino-β-keto amides have recently become easily accessible to us, thanks to a novel methodology developed within our group [12]. This gave us the opportunity to reinvestigate the cyclocondensation approach to indole-3-acetamides and to try the intramolecular Friedel-Crafts reaction on ethoxycarbonyl-protected γ-(N-phenyl)-β-keto amide 1 (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…N-protected γ-amino-β-keto amides have recently become easily accessible to us, thanks to a novel methodology developed within our group [12]. This gave us the opportunity to reinvestigate the cyclocondensation approach to indole-3-acetamides and to try the intramolecular Friedel-Crafts reaction on ethoxycarbonyl-protected γ-(N-phenyl)-β-keto amide 1 (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…The starting material ((3-Carbamoyl-2-oxo-propyl)-phenyl-carbamic acid ethyl ester, 1) was prepared from acetoacetamide and N-phenylglycine according to our previously published method [12]. Polyphosphoric acid (115% H 3 PO 4 basis, CAS No.…”
Section: Methodsmentioning
confidence: 99%
“…The problematic accessibility of ω-amino-β-keto anilides (1) by known methods is probably the main reason why these compounds have not been used as precursors to quinolin-2-ones until now. However, since a method developed recently in our laboratory provided easy access to these substrates [33], we decided to investigate their behaviour under Knorr-type conditions. After a quick screening of various acids and solvents, we arrived at polyphosphoric acid (PPA) as the optimal medium for the targeted cyclocondensation of 1 to 4-aminoalkylquinolin-2-ones 2.…”
Section: Resultsmentioning
confidence: 99%
“…The starting N-ethoxycarbonyl ω-amino-β-keto anilides (1) were prepared from the corresponding ω-amino acids and acetoacetanilide, according to our previously published procedure [33]. Polyphosphoric acid (115% H 3 PO 4 basis, CAS No.…”
Section: Methodsmentioning
confidence: 99%
“…Considering the current interest in this topic and the ongoing investigations of the structure-activity relationships, we saw an opportunity to contribute to the availability of structurally diverse Santacruzamate A analogues with our method for β-keto amide synthesis [9]. In a previous publication we demonstrated that this enamine-based domino approach provides access to β-keto amides IV functionalized with protected amino group in the side chain (Scheme 1, R 1 = H, Ph) [10]. If N-ethoxycarbonyl glycine is used as the amino acid component III in this methodology and R 1 is set to phenethyl, then the products IV would be structurally similar to Santacruzamate A, with introduced carbonyl functionality in the gamma-aminobutyric part and possible variation of the chain length by the choice of an appropriate R 1 substituent in the acetoacetamide I (Figure 1b).…”
Section: Introductionmentioning
confidence: 99%